All nonhomologous chromosomes and rearrangements in Saccharum officinarum × Saccharum spontaneum allopolyploids identified by oligo-based painting - Chai, Jin; Xue, Li; Lei, Jiawei; Yao, Wei; Zhang, Muqing; Deng, Zuhu; Yu, Fan (Frontiers in Plant Science, 2023)
Modern sugarcane cultivars (Saccharum spp., 2n = 100~120) are complex polyploids primarily derived from interspecific hybridization between S. officinarum and S. spontaneum. Nobilization is the theory of utilizing wild germplasm in sugarcane breeding, and is the foundation for utilizing S. spontaneum for stress resistance. However, the exact chromosomal transmission remains elusive due to a lack of chromosome-specific markers. Here, we applied chromosome-specific oligonucleotide (oligo)-based probes for identifying chromosomes 1-10 of the F1 hybrids between S. officinarum and S. spontaneum. Then, S. spontaneum-specific repetitive DNA probes were used to distinguish S. spontaneum in these hybrids. This oligo-fluorescence in situ hybridization (FISH) system proved to be an efficient tool for revealing individual chromosomal inheritance during nobilization. We discovered the complete doubling of S. officinarum-derived chromosomes in most F1 hybrids. Notably, we also found defective S. officinarum-derived chromosome doubling in the F1 hybrid Yacheng75-4191, which exhibited 1.5n transmission for all nonhomologous chromosomes. Altogether, these results highlight the presence of variable chromosome transmission in nobilization between S. officinarum and S. spontaneum, including 1.5n + n and 2n + n. These findings provide robust chromosome markers for in-depth studies into the molecular mechanism underlying chromosome doubling during the nobilization, as well as tracing chromosomal inheritance for sugarcane breeding.